The Implementation of SSI Model Assisted by Oray-Orayan Game Regarding Students' Argumentation Skills in Reproductive System Material - Monika Lailasari; Arfatul Makiyah; Suhendar Suhendar; Mira Mariana (Equator Science Journal, 2026)
Scientific argumentation skills are an essential 21st-century competency, yet remain relatively underdeveloped in biology education, particularly in reproductive system material rich with socio-scientific issues. This study investigated the effect of applying the Socio-Scientific Issues (SSI) model assisted by the Oray-Orayan game on high school students' argumentation skills. A quasi-experimental design with a nonequivalent control group was employed involving 50 students (25 experimental, 25 control) at SMA Muhammadiyah Sukabumi. Argumentation skills were measured using 10-item essay test based on Toulmin's six argumentation indicators (claim, data, warrant, backing, qualifier, rebuttal) for both pretest and posttest, and a student response questionnaire was administered to the experimental class. Statistical analysis using Mann-Whitney U test showed a significant difference between posttest scores of the experimental and control groups (Asymp. Sig. = 0.000 < 0.05). Implementation observation scores reached 94% (experimental) and 89% (control), both categorized as "Very Good." Student responses were consistently positive across all indicators. These findings confirm that the SSI model assisted by the Oray-Orayan game effectively enhances students' scientific argumentation skills in reproductive system material and can serve as an innovative, contextual, and meaningful alternative learning model in biology education.